Inovasi Pengembangan Penilaian Autentik Aspek Keterampilan di SMA Nazhatut Thullab - Muhammad Sholeh Hoddin (LP2M Institut Agama Islam Nazhatut Thullab Sampang, 2023)
This paper aims to describe the innovations in the development of authentic assessment of skills aspects carried out at Nazhatut Thullab High School. The approach used in this research is descriptive-qualitative. The data analysis technique used in this research is data reduction, data display, and verification. Furthermore, the researcher conducted an audit of the research results with the following steps: extension of participation, persistence/constant observation, triangulation, and peer-review through discussion. The results of this study indicate that the innovation of developing authentic assessments of skills aspects at Nazhatut Thullab High School resulted in a policy to develop two of the three authentic assessments of skills aspects, namely output-based performance assessments, and output-based project assessments, which are assessment models that are commonly carried out. by all educators, namely project assessment, and performance assessment by producing products, which in practice refers to the guidelines issued by the Government, with the obligation for all students to document all assessment processes until the end in video form and upload them to the YouTube channel each. The objectives of the video documentation process and uploading to the YouTube channel are (1) to make it easier for teachers to provide in-depth assessments (2) to provide IT education and (3) to provide them with basic entrepreneurial learning.